Mineral and Protein Screening of Some Wild Legumes of Dilling area (South Kordofan State, Sudan): مسح للعناصر المعدينة والبروتينات في بعض النباتات البقلية بمنطقة الدلنج (جنوب كردفان – السودان) - Gomma, Abd AlGabbar Nasir; Ibrahim, Widad Mohammed (Journal of Faculty of Education, 2021)
Mineral screening was carried out on leaves of seven wild leguminous plants namely: Tamarindus indica, Albizzia amara, Acacia laeta, Senna obtusifolia, Senna occidentalis, Phaseolus adenanthus and Crotalaria saltiana. The leaves have high protein content which ranges between 21.6% for Phaseolus adenanthus and 17.3% for Senna occidentalis. Mineral elements detected in appreciable quantities were Calcium, Magnesium, Potassium, Phosphorus, Sulfur and Iron. Manganese contents were very low and they range between 0.01% for Senna occidentalis and 0.03%for Tamarindus indica, Acacia laeta and Crotalaria saltiana. Analysis showed that these species had different levels of mineral and crude protein.